Expended energy based damage assessment of RC structures: new damage assessment methods - Vimala, Anthugari; Kumar, Ramancharla Pradeep (Journal of Structural Engineering, 2024)
Many past response analyses of the structures under earthquake excitations revealed that both the maximum displacements and the number of large-amplitude displacement responses cause higher damage to the structures. In the present study, a new methodology is proposed for seismic damage assessment of a reinforced concrete framed structure based on the energy dissipated by the structure along the completed displacement path. Three methods are proposed to assess the global damage state of the structure. In the proposed methods, the damage index is expressed at any instant of deformation as the ratio of the expended energy at the instant to the total energy dissipation capacity of the structure.